VNE-AFS:virtual network embedding based on artificial fish swarm - Qiang ZHU; Hui-qiang WANG; Hong-wu LV; Zhen-dong WANG (Tongxin xuebao)
Recently virtual network embedding problem had been proposed as a research challenge in the cloud computing environment.In order to reduce the costs,a virtual network embedding algorithms based on artificial fish swarm(VNE-AFS)was proposed.A binary combinatorial optimization model was built according to the constraints on nodes and links between virtual network and substrate network,and the artificial fish swarm algorithm was used to achieve the approximate optimal mapping.The simulation results indicate that the costs of substrate network and computation time are reduced and the success rate,average revenue of embedding and average usage of links are increased compared with the existing virtual network embedding algorithms.